Money Politics Prevention Strategy: Measuring the Effectiveness of Regulations on Campaign Logistics Distribution - Fitrianingsih Fitrianingsih; Yuli Yanti Daaris; Ikram Ikram; Emil Maulana; Buhari Buhari (Visi Pencerah Nusantara, 2026)
Corruption in vote buying poses a significant threat to democracy's integrity, particularly when campaign logistics are misused as a covert means of vote buying. This article evaluates the effectiveness of current regulations in distributing campaign logistics to curb vote-buying practices. A bibliometric analysis of 109 scientific publications and trends over the past five years indicates that existing regulations, including Law No. 7 of 2017 and various regulations issued by the General Elections Commission (KPU), remain insufficient to prevent such manipulation. The lack of strict oversight, the public's low political knowledge, and legal loopholes are exploited by politicians to disguise vote buying as social assistance programs. This article proposes a strategic approach that includes regulatory reform, the use of digital technology to monitor campaign logistics, political education, and increased public participation. Collaboration among stakeholders is crucial to establishing a clear oversight system and supporting fair and credible elections.